Review on the Epizootiological Situation on Highly Pathogenic Avian Influenza Globally and in Russia in 2023 - N. N. Vasil’tsova; A. S. Panova; V. N. Petrov; A. V. Danilenko; S. V. Svyatchenko; K. I. Ivanova; G. S. Onkhonova; N. I. Goncharova; A. B. Ryzhikov; V. Yu. Marchenko; Н. Н. Васильцова; А. С. Панова; et al. (Polar Biology, 2024)
The year 2023 saw a challenging epizootiological and epidemiological situation regarding highly pathogenic avian influenza. The virus affected 150 bird species and dozens of mammal species. More than 650 outbreaks were reported in poultry across 29 countries, resulting in the death or destruction of approximately 19 million specimens. There was a high incidence of the influenza among wild birds (approximately 3,000 outbreaks in 65 countries) and mammals (more than 16,000 cases). The majority of outbreaks in wild birds, poultry and mammals were caused by influenza A(H5N1) clade 2.3.4.4b viruses. Many countries in Europe, Asia, Africa, North and South America experienced the outbreaks throughout the year. For the first time, a polar bear death from A(H5N1) virus was documented. Moreover, molecular markers of virus adaptation to mammals were found in PB2 proteins of 50 % of influenza A(H5N1) viruses that caused the death of animals. During the year 2023, human infections with highly pathogenic avian influenza A(H5N1) viruses were reported in Cambodia, Chile, China, and the UK. In addition, human infections with A(H3N8), A(H5N6), A(H9N2) and A(H10N5) viruses were reported in China. In Russia in 2023, outbreaks among wild birds and poultry were registered in 25 regions, as well as an outbreak among fur seals in the Sakhalin Region. The stated outbreaks were caused by highly virulent influenza A(H5N1) clade 2.3.4.4b. Hemagglutinin sequences of all Russian viruses analyzed in this study in 2023 were genetically close to the WHO candidate vaccine strains A/Astrakhan/3212/2020 (H5N8), A/chicken/ Ghana/AVL-763_21VIR7050-39/2021 (H5N1) and A/American Wigeon/South Carolina/22-000345-001/2021 (H5N1). All studied A(H5N1) viruses were antigenically similar to the A/Astrakhan/3212/2020 vaccine strain. В 2023 г. ситуация в мире по высокопатогенному гриппу птиц в эпизоотологическом и эпидемиологическом плане была напряженной. Вирусом оказались инфицированы 150 видов птиц и десятки видов млекопитающих. Зарегистрировано более 650 ...